PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN LEVERAGE, TERHADAP NILAI PERUSAHAAN TRANSPORTASI - Sari, Mey Rina Putri Andika; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence of profitability, firm size, and leverage to the firm value. Thepopulation is Transportation Companies which are listed in Indonesia Stock Exchange in 2011-2014 periods.This research is based on the purposive sampling criteria and 10 go public companies have been obtained assamples; the total samples are 40 transportation companies. The data collection technique uses the secondarydata from Indonesia Stock Exchange. The data analysis method has been carried out by using multiple linearregressions analysis. The result of this research shows that (1) Profitability has influence to the firm value whichshows the capability of the company in gaining profit. When the ROE is getting larger, the profit level whichwill be achieved by the company is getting larger as well; (2) Firm size has an influence to the firm value itmeans that when the sales growth is getting higher, it will require great company resources; (3) Leverage has aninfluence to the firm value, it means that the management decision is to try to keep the leverage ratio not toohigh then the company applies internal financing.Keywords: Profitability, firm Size, leverage, firm value